2009
DOI: 10.1542/peds.2009-0964
|View full text |Cite
|
Sign up to set email alerts
|

Snacking in Children: The Role of Urban Corner Stores

Abstract: OBJECTIVE: Childhood obesity is higher among ethnic minorities. One reason may be the limited access to affordable, healthy options. The disparate prevalence of urban corner stores in low-income and high-minority communities has been well documented. There are no data, however, on what children purchase in these environments before and after school. The purpose of this study was to document the nature of children's purchases in corner stores proximal to their schools. METHODS: This was an observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 195 publications
(203 citation statements)
references
References 18 publications
5
195
1
2
Order By: Relevance
“…Os resultados mostraram que as crianças que participaram do estudo adquiriam, em média, 356 kcal por compra, podendo chegar a 712 kcal/dia e 3.560 kcal/semana para as crianças que compravam duas vezes ao dia, durante 5 dias da semana, nesses locais. Os alimentos mais populares eram os de baixo custo, altamente energéticos e com baixo valor nutritivo 23 .…”
Section: Distância (M)unclassified
“…Os resultados mostraram que as crianças que participaram do estudo adquiriam, em média, 356 kcal por compra, podendo chegar a 712 kcal/dia e 3.560 kcal/semana para as crianças que compravam duas vezes ao dia, durante 5 dias da semana, nesses locais. Os alimentos mais populares eram os de baixo custo, altamente energéticos e com baixo valor nutritivo 23 .…”
Section: Distância (M)unclassified
“…Each of these age groups should be studied separately in order to understand how they may interact with the FE differently. While there is some qualitative 19 and quantitative research in this area, [16][17][18] there is a need for more of both to better understand how children interact with their community and consumer nutrition environments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that children frequently purchase and consume energy-dense snack foods and sugar-sweetened beverages from stores near their school and home, and when they are guests in others' homes; however, there is limited qualitative research on the local FE of early adolescent children and their food purchasing decisions. [16][17][18][19] The purpose of this study was to examine how pre-and early adolescent (10-14 years old) children from a wide range of neighbourhoods interact with their local FE, with a focus on the foods and food sources they access and their locations. Children in this age group are developing independence and mobility within (and beyond) their home neighbourhoods but are somewhat geographically bound as they cannot yet drive.…”
mentioning
confidence: 99%
“…Unhealthy food and beverage products were widely available to children through food retailers. 97,98 Nevertheless, Wal-Mart announced encouraging steps in early 2011 to expand healthier options. 99 Only three trade associations are members or partners of the HWCF.…”
Section: Industry Trade Associations-limited Progress Achievedmentioning
confidence: 99%